Державна інвестиційна політика як інструмент відродження села - Сердюк, Т. В.; Новохацька, Л. В. (Ways to Improve Construction Efficiency, 2014)
This paper analyzes the place of public investment in sources of financing rural social infrastructure, identified shortcomings of government policy on the development of social infrastructure in rural areas, discussed means of improving existing system financial provision of rural infrastructure.